Diversity of water management systems: Examples from Hmong and Thai communities in Mae Sa Watershed northern Thailand - Andreas Neef (2018)
In Thailand water is widely percieved as an open access resource. It is also common belief that organization of highland irrigation in northern Thailand is characterized by a relatively simple structure, and that local communities are not able to adjust their management practises to new realities. The existence of diverse forms of control, ownership and rights of use relating to water resources is widely ignored. This goes along with a stereotypical and static picture of highland people-and ethnic minorities in particular-as being environmentally destructive and culturally backward. These misperceptions fail to recognize that economic, institutional and social conditions are rapidly changing in the highlands of northern Thailand. These changes bring about a range of cultural and economic adjustments at the local level, which is also reflected in the management of water resources. The present article argues that cultural identities and social norms in the highlands are fluid, that local communities continuously adapt their water management practices to new circumstances, and that the outcomes of this process are not always beneficial to sustainability and distributional equity.